KUALITAS PELAYANAN RAWAT JALAN POLI KANDUNGAN DI RS SITI KHODIJAH MUHAMMADIYAH CABANG SEPANJANG SIDOARJO - Firdausi Nuzula; Annisa Wigati Rozifa; Irma Maya Puspita (Rena Cipta Mandiri, 2025)
Improving the quality of midwifery services is essential to ensure safety and comfort for pregnant women during antenatal care (ANC). This study analyzed the effectiveness of service management based on five SERVQUAL dimensions: tangibles, reliability, responsiveness, assurance, and empathy. Thirty-five pregnant women who attended the obstetrics outpatient clinic at Siti Khodijah Muhammadiyah Hospital, Sepanjang Branch, participated as respondents. Data were collected using a validated and reliable questionnaire. The results showed that all service aspects had a mean score above 1.8, categorized as “good,” with empathy and tangibles achieving the highest averages. Overall, 94% of respondents expressed satisfaction. However, utilization of the Maternal and Child Health (MCH) Handbook remained suboptimal. Strengthening patient communication and educational facilities, along with developing interpersonal skills among healthcare workers, is recommended.